Working Women in the Sandwich Generation Theories, Tools and Recommendations for Supporting Women's Working Lives - Rajahonka, Mervi (Emerald Points, 2022)
Women more often than men take care of their ageing relatives together with their own children or grandchildren. These Sandwich Generation (SG) women constitute an expanding vulnerable group on the labour market at higher risk of discrimination, work-family conflict, burnout, and withdrawal from the labour market and unemployment. Working Women in the Sandwich Generation helps present a clearer view of how to support this group both now and in the future. Beginning with a presentation of quantitative and qualitative research that sheds light on the SG situation in Poland, Finland and Flanders, this volume provides insights into various components from the SG life domains such as personal development and learning, connection to the labour market, coping strategies, resources, and energy drainers. In the second part the book provides tools for SG women, their supervisors, educators, and coaches to help manage challenging situations and improving wellbeing at work. Working Women in the Sandwich Generation then introduces the results of international comparative research the purpose of which was to identify and characterise the SG in five European countries before concluding with recommendations for supervisors and policy makers in supporting SG women.